Efficacy of intermittent exposure to bright light for treating maladaptation to night work on a counterclockwise shift work rotation - Heidi M Lammers-van der Holst; James K Wyatt; Todd S Horowitz; John C Wise; Wei Wang; Joseph M Ronda; Jeanne F Duffy; Charles A Czeisler (Nordic Association of Occupational Safety and Health (NOROSH), 2021)
OBJECTIVES: Rotating shift work is associated with adverse outcomes due to circadian misalignment, sleep curtailment, work-family conflicts, and other factors. We tested a bright light countermeasure to enhance circadian adaptation on a counterclockwise rotation schedule. METHODS: Twenty-nine adults (aged 20-40 years; 15 women) participated in a 4-week laboratory simulation with weekly counterclockwise transitions from day, to night, to evening, to day shifts. Each week consisted of five 8-hour workdays including psychomotor vigilance tests, two days off, designated 8-hour sleep episodes every day, and an assessment of circadian melatonin secretion. Participants were randomized to a treatment group (N=14), receiving intermittent bright light during work designed to facilitate circadian adaptation, or a control group (N=15) working in indoor light. Adaptation was measured by how much of the melatonin secretion episode overlapped with scheduled sleep timing. RESULTS: On the last night shift, there was a greater overlap between melatonin secretion and scheduled sleep time in the treatment group [mean 4.90, standard deviation (SD) 2.8 hours] compared to the control group (2.62, SD 2.8 hours; P=0.002), with night shift adaptation strongly influenced by baseline melatonin timing (r^2=-0.71, P=0.01). While the control group exhibited cognitive deficits on the last night shift, the treatment group's cognitive deficits on the last night and evening shifts were minimized. CONCLUSIONS: In this laboratory setting, intermittent bright light during work hours enhanced adaptation to night work and subsequent readaptation to evening and day work. Light regimens scheduled to shift circadian timing should be tested in actual shift workers on counterclockwise schedules as a workplace intervention.